The design of a new industrial strategy - Kennedy, Kieran A. (Statistical and Social Inquiry Society of Ireland, 1983)
The publication of the Telesis Report (1982) occurs at a critical time for the Irish economy. Over the next few years the growth of domestic and foreign markets is likely to be sluggish. A satisfactory growth of manufacturing output can be achieved, therefore, only by increasing market share, particularly in export markets. This in turn implies that progress depends on exploiting more effectively whatever competitive advantages we have and on improving these competitive advantages. Moreover, the aggregate volume of mobile international projects may be reduced and there is likely to be intensified international competition for such projects. Such circumstances suggest the need to concentrate relatively more than in the past on the development of domestic enterprise.
Symposium on Industrial Policy in Ireland
Read before the Society, 2 December 1982
Keywords: Irish industrial policy; Irish Development Authority; Industrial development; Export-led growth; Domestic manufacturing; 314.15